Modeling the Behaviour of Corporate Demand for Credit in Mauritius before and after the Global Financial Crisis Under Conditions of Excess Liquidity by Banks - Prayagsing, Chakeel Coomar (Archives of Business Research, 2020)
This Paper proves that the global financial crisis (GFC) has had a major influence in altering the pattern and subsequent demand for corporate finance in Mauritius. By applying probability models, it is found that bonus issuance is a key factor that influences the demand and supply for both debt and equity financing. Firms consider debt repayment variable of upmost essence to loan application and provision responses. Large companies, comprising of entities falling under the wing of the manufacturing, industrial and retail sector found ease in obtaining bank loans prior to the crisis due to the positive rating and nature of their respective businesses. Conversely, small and medium enterprises found themselves relaying heavily on startup loans, of limited amounts, as they failed to qualify for greater loan applications due to their inability to meet the adequate requirements. Corporate entities on their end, had a much greater preference for equity financing prior to the crisis. The aftermath of the crisis nevertheless negatively influenced the pattern of financing for all categories of businesses. A more regulated framework was adopted by banks, on an international level which caused banks to be more cautious and limited in providing finance to entities. Even with excess liquidity, banks have declined demand for bank loans.